Pembagian Wilayah PPAT oleh Badan Pertanahan Nasional (BPN) Kota Surabaya Berkaitan dengan PP No. 37 Tahun 1998 - Camelia Parameswari, Rayfa; Christian Orey Singal, Laurentius Kevin; Christianti Supardi, Septia Angelin (UNES Law Review, 2024)
BPN has partners to help carry out its duties and functions, one of which is PPAT, which is a public official who is given the authority to make authentic deeds regarding land rights, which has a working area that has different rules in Government Regulation Number 24 of 2016 which regulates PPAT's working area is one provincial area, whereas in Regulation of the Head of the National Land Agency Number 1 of 2006 it is one working area of the Land Office. This resulted in losses for the PPAT that forced to follow the BPN. This writing was carried out using the Statute Approach and Conceptual Approach, which aims to obtain legal certainty regarding the PPAT work area that should be followed. From the discussion, it can be seen that the source of BPN's authority to divide the PPAT area is based on the Head of Land Agency Regulation Number 1 of 2006 which regulates the work area of PPAT which follows the land office, and that the legal relationship between PPAT and BPN is specifically in the scope of the transfer of land rights is a horizontal legal relationship (mitra) so it should not be appropriate for one institution to impose its will which is contrary to the applicable laws and regulations